-ALMOST DIFFERENCE SEQUENCES OF FUZZY NUMBERS - Altın, Yavuz (My University, 2016)
In this study, we introduce several sets of sequences of fuzzy numbers using various sequencesandin the class and examine some inclusion relations among these sets.
Keywords: Matematik